2018
DOI: 10.1186/s13071-018-2986-2
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics of the oriental latrine fly Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae): temporal fluctuation and reproductive potential

Abstract: BackgroundChrysomya megacephala is a blow fly species of medical and forensic importance worldwide. Understanding its bionomics is essential for both designing effective fly control programs and its use in forensic investigations.MethodsThe daily flight activity, seasonal abundance related to abiotic factors (temperature, relative humidity and rainfall) and reproductive potential of this species was investigated. Adult flies were sampled twice a month for one year from July 2013 to June 2014 in three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
11
0
4
Order By: Relevance
“…A second hypothesis is that males become less attracted to papaya bait between bird breeding seasons. Although field studies in Galapagos have confirmed that young and old males are attracted to yeasts and fermenting fruits [18,26], it is possible that males outside the bird breeding season need less food or seek a different food than females, as occurs with some muscid, calliphorid and tephritid fruit flies [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…A second hypothesis is that males become less attracted to papaya bait between bird breeding seasons. Although field studies in Galapagos have confirmed that young and old males are attracted to yeasts and fermenting fruits [18,26], it is possible that males outside the bird breeding season need less food or seek a different food than females, as occurs with some muscid, calliphorid and tephritid fruit flies [27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some authors have demonstrated the importance of biases associated with small bait traps, such as those caused by weather factors, height of traps, and position, as well as biased sex ratios and age-classes of captured Diptera [ 11 , 39 , 40 ]. Furthermore, the flight patterns of Calliphoridae are known to vary throughout the day [ 41 , 42 ]. As such, from an experimental standpoint, small bait traps which sample constantly are more likely to capture taxa which may not be active when the carcasses are being sampled.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommend that the isotope signatures for the body in question should also be determined so that they can be compared with the signatures from the entomological specimens from the crime scene. [25,27,31] easy to do preparation mainly just for females rough classification into categories 3…”
Section: Discussionmentioning
confidence: 99%
“…This kind of staging is also established for forensically relevant Muscidae or blow flies like Chrysomya spp. [28][29][30][31] The dependence on protein sources for egg formation and the absence of oviposition sites, which could delay the egg formation, but also the numbers of ovarian cycles in female flies, are a disadvantage of these methods, as they are the source of significant variation [12]. Moreover, Gillies and Wilkes [32] highlighted the lack of reproducibility of this technique across species and between technicians during their work on Anopheles spp.…”
Section: Introductionmentioning
confidence: 99%